2017
DOI: 10.1055/s-0036-1588479
|View full text |Cite
|
Sign up to set email alerts
|

AlCl3-Catalyzed Intramolecular Hydroarylation of Arenes with Alkynes

Abstract: Herein, we wish to report the main-group metal Lewis acid catalyzed intramolecular hydroarylation of arenes with alkynes. This cyclization proceeds efficiently in the presence of a catalytic amount of AlCl3, affording phenanthrenes in moderate to excellent yields. The catalyst is cheap and nontoxic. The functional-group tolerance is high. A plausible electrophilic aromatic substitution reaction mechanism is proposed for this transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…[126] The desired products were produced with good to exceptional yields and great diastereoselectivity (up to > 99 : 1 dr) using a wide variety of internal and terminal alkenes, including electron-rich as well as electron-deficient alkenes. It was also observed that iron catalysis had a strong catalytic activity for 1,2-oxyacetoxylation of terminal alkynes (132).…”
Section: Chemistryselectmentioning
confidence: 97%
See 1 more Smart Citation
“…[126] The desired products were produced with good to exceptional yields and great diastereoselectivity (up to > 99 : 1 dr) using a wide variety of internal and terminal alkenes, including electron-rich as well as electron-deficient alkenes. It was also observed that iron catalysis had a strong catalytic activity for 1,2-oxyacetoxylation of terminal alkynes (132).…”
Section: Chemistryselectmentioning
confidence: 97%
“…1,3‐Naphthoxazines ( 149 ) were produced diastereoselectively, as a result of the following reactions of 1‐(‐aminoalkyl)‐2‐naphthols with PIDA by the research group of Karade (Scheme 52). [132] This reaction illustrated how, in the absence of transition metals, the C−O bond could be formed by cross dehydrogenative coupling (CDC). The optimized reaction parameters are: PIDA (2.2 equiv.)…”
Section: Applications Of Phenyliodine(iii)diacetatementioning
confidence: 98%